Penicillamine-Induced Membranous Nephropathy in an Adolescent with Wilson's Disease - Catarina Fernandes; Mariana Duarte; Patrícia Ferreira; Cristina Gonçalves; Ana Paula Serrão; Rute Baeta Baptista (Publicações Ciência e Vida, 2022)
Membranous nephropathy may present in any age group. While it is one of the most common causes of adult nephrotic syndrome, it is a rare histologic entity in the paediatric population. In adults it is more commonly classified as primary or idiopathic. In contrast, among children and adolescents, it is more frequently secondary to systemic disorders or drug exposures. One of the potentially implicated drugs is penicillamine, which has long been used as first-line therapy for symptomatic children with Wilson's disease. We report a case of an adolescent treated with penicillamine for Wilson's disease, who presented with overt nephrotic syndrome due to membranous nephropathy. As most of our knowledge about children and adolescents with membranous nephropathy has been based on extrapolations from adult studies, paediatric case reports may provide useful insights. We also aimed to emphasize the importance of proteinuria close monitoring in patients under treatment with penicillamine to allow for timely consideration of the drug withdrawal.